PENGARUH MODEL LEARNING CYCLE 5E TERHADAP MINAT DAN HASIL BELAJAR SISWA PELAJARAN MATEMATIKA KELAS V SEKOLAH DASAR - Putri Praandini, Tiyah; Rasilah; Dede Hadiansah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education is an important process for passing on cultural values ​​and developing students' potential holistically, including spiritual, intellectual and skills aspects. In the learning context, the use of appropriate learning models can increase student interest and learning outcomes. The Learning Cycle 5E learning model (Engagement, Exploration, Explanation, Elaboration, Evaluation) emphasizes active student involvement, so it is effective in facilitating understanding of concepts and improving learning achievement. From the percentage obtained, it shows that 65% of the total number of students, 32 students, still shows low interest in learning. This means that only 11 students have shown interest in studying the eye math. Another cause is that the learning model applied is less attractive. Therefore, students become passive and tend to remain silent because they do not understand the material, which has an impact on students' low interest in learning. (Juniarti & Affandi, 2020). From the results of interviews with class V teachers, students' learning outcomes in mathematics were still below the specified minimum standard scores, of the 32 class V students at SDN 3 Kertasura who had achieved 34% completion of the KKM, 11 students, while 65% had not completed the KKM as many as 21 students. The application of the 5E Learning Cycle model is proposed to overcome this problem. This model not only improves understanding of the material, but also encourages students' active participation in the learning process. By providing a fun and relevant learning experience, this model is expected to significantly increase student interest and learning outcomes, especially in mathematics subjects.